Logistics and transport infrastructure of Ukrainian regions bordering the eu: diagnostics and directions of developme - Ivashko, Olena A.; Sak, Tetiana V.; Mylko, Inna P.; Chulipa, Ihor D. (My University, 2024)
The current trends in the development of international trade in Ukraine and the participation of individual regions in foreign trade in goods are studied. Theoretical aspects of logistics and transport infrastructure and its components are considered. International indices for assessing the level of development of logistics and transport infrastructure are analyzed. The logistics performance index (LPI) is used to assess the efficiency of the logistics chain in a number of countries. The development of logistics and transport infrastructure in the regions of Ukraine bordering the EU is diagnosed. Indicators of the logistics and transport infrastructure are calculated and grouped by the following components: border infrastructure, including the analysis of checkpoints, roadside service infrastructure, and the institutional omponent of the logistics and transport infrastructure for freight transportation. The efficiency of the logistics and transport infrastructure is assessed in terms of individual structural elements. The problems and directions of development of the transport and logistics infrastructure of the regions of Ukraine bordering the EU are identified.
Keywords: diagnostics of logistics infrastructure; logistics and transport infrastructure